COMPARISON OF ORAL IRON AND INJECTABLE IRON IN %HE PWVENTION OF IRON DEFICIENCY ANAEMIA IN PIGLETS - ADESEHINWA, A. O. K.; OGUNSANMI, A. O.; Qmitoyin, B.O. (Nigerian Journal of Animal Science, 2023)
An oral iron compound or an injectable iron (100mg iron per treatment) was administered to baby pigs on da 3 - postfarrowing and were compared with untreated littermates There was no signizcant difference (P > 0.05) between the pigs receiving the oral and the negative control in serum iron or total iron binding capacity. Pigs that received iron by injection had significantly higher serum iron and packed cell volume (P < 0.05) and a lower total iron Rding capacity compared with pigs given oral iron or untreated control (P < 0.05)